Intervenção por telefone como estratégia para manejo da ansiedade durante tratamento radioterápico: um ensaio clínico randomizado - Stamm, Bruna (2015)
Radiotherapy treatment can generate negative impacts, including anxiety, which can interfere with the emotional balance of patients and families. The study is a randomized clinical trial to evaluate the effects of a telephone intervention in in patient anxiety scores in radiotherapy and their families. The population consisted of 20 patients in the Intervention Group, 19 patients in the Control Group and their respective families, who underwent radiotherapy at the University Hospital of Santa Maria, in Rio Grande do Sul, in the period from April to July 2014. For data collection used a questionnaire with sociodemographic and clinical issues, the State-Trait Anxiety Inventory and a post-intervention interview. The interventions were conducted through telephone contacts. The data were analyzed using the Statistical Package for Social Sciences for Windows version 21.0. The Student t test for paired samples was used to compare the pre and post-intervention. The association of Anxiety-Trait and State levels with the other study variables were performed using Pearson correlation test. It was performed multiple linear regression for the studied variable. The level of significance was p value <0,05. Patients in the Intervention and Control Groups respectively were mostly female (55,0% and 53,9%), with an average age of 62,2 (± 11,8) and 63,0 (± 10,3) years, and the prevalence of head and neck cancer (30,0% and 41,5%). The family of the Intervention and Control Groups were mostly female (85,0% and 57,9%), with an average age of 47,0 (± 13,8) and 54,5 (± 11, 9) years and children degree of kinship (GI: 50,0%) and husband or partner (GC: 42,1%). At the beginning of radiotherapy treatment, the most patients and families Intervention Group showed a moderate score of Anxiety-Trait and State, and patients and families in the Control Group showed a moderate score for Anxiety-Trait Anxiety and down to the State. The results are statistically significant and show that the telephone intervention decreased anxiety scores of the intervention group patients after the phone calls (p <0,005). For family members of both groups there were no significant differences in pre and post-intervention. Predictive factors for Anxiety-Trait of the Intervention Group patients were the number of radiotherapy sessions (p <0,000), and for the Anxiety-State predictors were the level of education (p <0.018), the disease diagnosis time in months (p <0,048) and the number of sessions of radiotherapy (p <0,000). Patients and relatives who received the intervention evaluated it as positive, and important to remedy the fundamental questions related to radiotherapy treatment. It is concluded that the telephone intervention was effective in reducing the anxiety scores of patients and relatives during radiotherapy treatment. It is expected that the study will contribute to the reflection on innovative and technological practices of nursing care and the redirection and development of new care strategies in radiotherapy treatment to the patients and their relatives.